Propofol reduces anoxia-reoxygenation-induced injury of cardiomyocytes - CHEN Si, YANG Fu-guo, PENG Hong-jun, CAO Wei-le, WANG Zhen-yu (Jichu yixue yu linchuang, 2022)
Objective To investigate the effect of propofol (Pro) on cardiomyocyte damage induced by anoxia-reoxygenation through regulating JNK/p38 MAPK pathway. Methods Divided the cells into control group, anoxia-reoxygenation (A/R) group, anoxia-reoxygenation+propofol of low, medium and high dose (A/R+Pro-L, A/R+Pro-M, A/R+Pro-H) group, anoxia-reoxygenation+propofol+p38 MAPK pathway inhibitor (A/R+Pro+SB203580) group. Flow cytometry was used to detect cell apoptosis; Western blot was used to detect the expression of Bcl-2, Bax, cleaved caspase-3 and JNK/p38 MAPK signaling pathway related proteins; ELISA was applied to detect LDH content, MDA content, SOD activity and CAT activity. Results In A/R group Bcl-2 protein expression SOD and CAT activity were significantly inhibited cell apoptosis rate, Bax protein, cleaved caspase-3 protein expression, LDH, MDA, p-JNK protein, p-p38 MAPK protein expression were promoted(P＜0.05). Compared with A/R group, A/R+Pro-L group, A/R+Pro-M group, A/R+Pro-H group all showed significantly promoted cell Bcl-2 protein expression, SOD, CAT activity; inhibition of cell apoptosis, Bax protein, cleaved caspase-3 protein, LDH, MDA, p-JNK protein and p-p38 MAPK protein(P＜0.05). Compared with the A/R+Pro group, the A/R+Pro+SB203580 group showed significantly promoted cell Bcl-2 protein expression, SOD, CAT activity and inhibited cell apoptosis, p-JNK protein, p-p38 MAPK protein, Bax protein, cleaved caspase-3 protein, LDH and MDA (P＜0.05). Conclusions Propofol may slow down anoxia-reoxygenation induced cardiomyocyte apoptosis and oxidative stress through regulating the JNK/p38 MAPK pathway.